Graphdiyne-supported single-cluster electrocatalysts for highly efficient carbon dioxide reduction reaction. Issue 4 (6th January 2022) - Ge, Pingji; Zhai, Xingwu; Liu, Xiaoyue; Liu, Yinglun; Yang, Xiaodong; Yan, Hongxia; Ge, Guixian; Yang, Jueming; Liu, Yunhu
Abstract : The Cr3 @GDY possesses the best catalytic performance with a remarkably low rate-limiting step of 0.39 eV toward the CO2 product. Abstract : The electrochemical CO2 reduction reaction (CO2 RR) has become a promising technology to resolve globally accelerating CO2 emissions and produce chemical fuels. In this work, the electrocatalytic performance of transition metal (TM = Cu, Cr, Mn, Co, Ni, Mo, Pt, Rh, Ru and V) triatomic clusters embedded in a graphdiyne (GDY) monolayer (TM3 @GDY) for CO2 RR is investigated by density functional theory (DFT) calculations. The results indicate that Cr3 @GDY possesses the best catalytic performance with a remarkably low rate-limiting step of 0.39 eV toward the CO2 product, and it can also effectively suppress the hydrogen evolution reaction (HER) during the entire CO2 RR process. Studies on the rate-limiting steps (CHO* + H + + e − → CHOH) of Cr n @GDY ( n = 1–4) structures demonstrate that the high catalytic performance is attributed to the strong synergistic reaction of three Cr atoms interacting with the C atom for the Cr3 @GDY structure. The strong synergistic reaction gives rise to the weakest interaction between O–Cr atoms, which leads to the strongest interaction between O–H atoms and makes the hydrogenation process easier for the Cr3 @GDY structure. Furthermore, ab initio molecular dynamics simulations (AIMD) at 500 K reveal the high thermodynamic stability of the Cr3 @GDY structure. These studies may provide a new approach for designing highly efficient electrocatalysts for the CO2 RR under ambient conditions.